2015
DOI: 10.1007/s00125-015-3722-5
|View full text |Cite|
|
Sign up to set email alerts
|

The new biology of diabetes

Abstract: Until recently, type 2 diabetes was seen as a disease caused by an impaired ability of insulin to promote the uptake and utilisation of glucose. Work on forkhead box protein O (FOXO) transcription factors revealed new aspects of insulin action that have led us to articulate a liver- and beta cell-centric narrative of diabetes pathophysiology and treatment. FOXO integrate a surprisingly diverse subset of biological functions to promote metabolic flexibility. In the liver, they controls the glucokinase/glucose-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
72
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 103 publications
2
72
0
1
Order By: Relevance
“…The balance between the activating and repressive functions of FOXO1 is crucial in the liver since, by inducing G6pc and by inhibiting Gck , FOXO1 regulates the G6pc / Gck ratio, intracellular glucose-6-phosphate levels, and hepatic glucose handling (Haeusler et al, 2014; Pajvani and Accili, 2015). Unlike previous studies showing that insulin induction of Gck expression requires the recruitment of transcriptional activators on Gck promoter (Foretz et al, 1999; Kim et al, 2004, 2009; Roth et al, 2004), the present data show that it requires clearance of a FOXO1 corepressor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The balance between the activating and repressive functions of FOXO1 is crucial in the liver since, by inducing G6pc and by inhibiting Gck , FOXO1 regulates the G6pc / Gck ratio, intracellular glucose-6-phosphate levels, and hepatic glucose handling (Haeusler et al, 2014; Pajvani and Accili, 2015). Unlike previous studies showing that insulin induction of Gck expression requires the recruitment of transcriptional activators on Gck promoter (Foretz et al, 1999; Kim et al, 2004, 2009; Roth et al, 2004), the present data show that it requires clearance of a FOXO1 corepressor.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown beneficial effects of FOXO1 inhibition on diabetic hyperglycemia by reducing hepatic glucose production. However, these benefits can be offset by an increase in hepatic fat content (Pajvani and Accili, 2015). We have discovered small molecules with the ability to fine-tune the FOXO1 activator/repressor balance and alter the ratio of G6pc to Gck .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have proposed a theory of ␤-cell dysfunction that attempts to reconcile diverse etiologies under a single mechanism and incorporates the role of insulin resistance in the process (4). We have shown that FoxO, a family of transcription factors with important roles in peripheral insulin signaling (5), also integrate various aspects of ␤-cell biology.…”
mentioning
confidence: 99%
“…1 In normal physiology, fasting triggers the release of glucagon from pancreatic α-cells, which stimulates gluconeogenesis and glycogenolysis to maintain normoglycemia. 2 In the postprandial state, pancreatic β-cells dial up insulin levels to block hepatic glucose production 35 and utilize excess glucose for long-term energy storage in the liver in the form of glycogen, and indirectly, triglycerides.…”
Section: Introductionmentioning
confidence: 99%